Histopathological Spectrum of Ovarian Tumors at Tertiary Care Hospital – A Three Year Retrospective Study of 45 Cases - Singh, Ritu Radheyshyam; Dholakia, Aditi Dharmesh; Shah, Khushbu Mehulkumar; Kadakia, Stuti Samir (Annals of Pathology and Laboratory Medicine, 2024)
Background The ovaries are paired intra-pelvic adnexal organs of the female reproductive system involved in many important functions of the body. No organ of the body except the ovary gives rise to such a galaxy of neoplasms​​. Histopathological examination of the biopsy material is the mainstay of diagnosis, which determines the prognosis and behavior of neoplasm​​​​. Material and Methods This was a retrospective observational study. A total of 45 cases were studied. All the cases of ovarian tumors were studied with respect to age of presentation, clinical symptoms, and morphological classification. Data thus collected were analyzed and compared with other study findings. Results A total of 45 ovarian tumor cases were studied. Surface epithelial tumors were the most common ovarian tumor, constituting 53.3%, followed by germ cell tumors at 31.3%, and sex cord-stromal tumors at 15.5%. Among surface epithelial tumors, serous tumors were the most common. Abdominal pain remained the most common clinical presentation. Conclusion Ovarian tumors are the second most common neoplasm in the female genital tract following cervical cancer. Though benign tumors are more common than malignant tumors, it is important to detect the tumor at its early stage. Histopathological findings along with immunohistochemistry are helpful in early diagnosis of ovarian tumors.